2012
DOI: 10.1292/jvms.11-0302
|View full text |Cite
|
Sign up to set email alerts
|

Slow Recovery of Blood Glucose in the Insulin Tolerance Test during the Prepartum Transition Period Negatively Impacts the Nutritional Status and Reproductive Performance Postpartum of Dairy Cows

Abstract: AbSTRACT. In peripartum dairy cows, insulin resistance (IR) increases to adjust the direction of energy to lactation after calving. To investigate the effect of prepartum IR on postpartum reproductive performance, the insulin tolerance test (ITT) was applied to 15 cows at 3 weeks (Pre21) and 10 days (Pre10) before the predicted calving date. blood glucose area under the curve (AUC glu ) within 120 min after administration of 0.05 IU/kg-BW insulin was calculated. The occurrence of first ovulation, days to first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
3
5
0
1
Order By: Relevance
“…The measured activities of AST, GGT, and GLDH corresponded with previous reports (Wille et al, 2010;Lee et al, 2012). In general, liver-associated variables were not affected by barley feeding in this study.…”
supporting
confidence: 92%
“…The measured activities of AST, GGT, and GLDH corresponded with previous reports (Wille et al, 2010;Lee et al, 2012). In general, liver-associated variables were not affected by barley feeding in this study.…”
supporting
confidence: 92%
“…Therefore, the detailed changes in blood glucose in dairy cows during the ITT have not yet been elucidated. Our previous study indicated a relationship between a smaller dose of insulin injection at ITT for pregnant dairy cows and their pp performance [ 22 ]. As the calving day approached, our data showed that increased decline of blood glucose 120 min after the administration of insulin was associated with liver dysfunction and lower fertility during the pp period owing to the slow glucose recovery [ 22 ].…”
mentioning
confidence: 99%
“…By contrast, the concentration of branched chain amino acids such as valine and isoleucine was by 15.5 % (P<0.01) and 5.4 % respectively lower than in healthy animals. It is known that valine and isoleucine are essential amino acids, which are metabolized mainly in muscle tissue and play significant role in energy metabolism, in particular in the formation and deposition of glycogen [3]. Thus, it can be argued that the imbalance of the amino acid composition of the blood in cows suffering from ketosis is an unfavorable factor for the course of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Це свідчить про посилення глюконеогенезу у період енергетичного дефіциту за рахунок ліполізу та протеолізу. Водночас у плазмі крові хворих корів було зареєстровано вищий вміст кетогенних амінокислот та нижчий -глікогенних: вміст фенілаланіну, тирозину та лейцину зростав на 22,2 % (P<0,05), 3 Ключевые слова: КОРОВЫ, КЕТОЗ, ГЛЮКОНЕОГЕНЕЗ, МЕТАБОЛИЗМ УГЛЕВОДОВ, АМИНОКИСЛОТЫ, ИНСУЛИН, КОРТИЗОЛ Ketosis is a disease of ruminants characterized by profound metabolic disorders (mainly of carbohydrates, lipids and proteins) and accompanied by increased formation and a sharp increase in the content of ketone bodies in blood, urine and milk. There is a characteristic complex group of symptom in which ketonemia, ketonuria and ketonolactia are the main signs at the onset of the disease in cows [5].…”
unclassified
See 1 more Smart Citation